RANCANG BANGUN SISTEM KENDALI JARAK JAUH NUTRISI TANAMAN HIDROPONIK BERBASIS INTERNET OF THINGS - Zulfa Fahrunnisa; Eka Maulana; n/a Rahmadwati (Jurnal Mahasiswa TEUB, 2023)
Hydroponics is a method of cultivating plants without using soil media. Hydroponics utilizes water/nutrient mineral solutions needed by plants and other materials as a substitute for soil media. Plants need the right amount of nutrients to grow and develop optimally. This research aims to design a tool that can provide the number of nutrients automatically with nutrient levels that can be adjusted remotely with the concept of the Internet of Things. The control system used is Mamdani fuzzy logic withinput offsets for nutrient content and water level in the reservoir, as well as output for the duration of the nutrient and water pumps to reach a setpoint that can be determined via the Blynk IoT platform. The results showed an accuracy of 93.14% for nutrient control and 97.83% for water level control in reaching the setpoint. Keywords: Fuzzy Logic, Hydroponics, Internet of Things, Nutrition Control System.